2011
DOI: 10.1007/s10802-011-9542-2
|View full text |Cite
|
Sign up to set email alerts
|

Parental Behaviors During Family Interactions Predict Changes in Depression and Anxiety Symptoms During Adolescence

Abstract: This study investigated the prospective, longitudinal relations between parental behaviors observed during parent-adolescent interactions, and the development of depression and anxiety symptoms in a community-based sample of 194 adolescents. Positive and negative parental behaviors were examined, with negative behaviors operationalized to distinguish between observed parental expressions of aggression and dysphoria. Results showed that higher levels of parental aggression prospectively predicted higher levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
4
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 54 publications
9
102
4
1
Order By: Relevance
“…These simultaneous changes can increase the vulnerability for developing symptoms of depression, known to be prevalent during mid-teens, [1] increasing the risk for negative outcomes, including functional impairment, distress, poorer quality of life, suicidal ideation and the trajectory to a clinical depression in adulthood. [1][2][3] The World Health Organization identified depression as the most common mental health disorder in adolescence [4] with subthreshold depression increasing the risk for a diagnosis of depression in this age group. [5] Understanding depression and identifying symptoms within this age group is very important in order to render preventive measures and treatment strategies.…”
Section: Articlementioning
confidence: 99%
“…These simultaneous changes can increase the vulnerability for developing symptoms of depression, known to be prevalent during mid-teens, [1] increasing the risk for negative outcomes, including functional impairment, distress, poorer quality of life, suicidal ideation and the trajectory to a clinical depression in adulthood. [1][2][3] The World Health Organization identified depression as the most common mental health disorder in adolescence [4] with subthreshold depression increasing the risk for a diagnosis of depression in this age group. [5] Understanding depression and identifying symptoms within this age group is very important in order to render preventive measures and treatment strategies.…”
Section: Articlementioning
confidence: 99%
“…This life stage can be marked by mental illness and declining life satisfaction (Andersen and Teicher 2008;Aquilino and Supple 2001), but can equally be an ''age of opportunity'' (Steinberg 2014) from which a young person emerges with thriving mental health and a positive identity in adulthood (Keyes 2006;Park 2004). Research has indicated that parenting can influence adolescents' mental health trajectories (Schwartz et al 2012a. In particular, positive parenting practices such as being warm, responsive, and autonomy-granting are related to higher self-esteem, enhanced life satisfaction, and greater wellbeing in teens (Baumrind 1991;DeVore and Ginsburg 2005;Milevsky et al 2007;Sanders et al 2003;Whittle et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Research has also demonstrated that depressive symptoms in adolescence are significantly and negatively associated with parental emotional support. Lower levels of positive parental behaviors also prospectively predicted adolescent depressive symptoms (Schwartz et al, 2012).…”
Section: Explanations Concerning Etiological Relationships Though Almentioning
confidence: 91%
“…Maternal and paternal emotional support are significantly associated with adolescent depressive symptoms (Houltberg, Henry, Merten, & Robinson, 2011) and lower levels of positive parental behaviors have prospectively predicted adolescent depressive symptoms at a 2.5 year follow-up (Schwartz et al, 2012). Low levels of parental support have been found to correlate amongst adolescents and young adults experiencing high levels of depressive symptoms (i.e., Holahan et al, 1995;Pettit et al, 2011;Stice et al, 2004).…”
Section: Explanations Concerning Etiological Relationships Though Almentioning
confidence: 99%